The aesthetic movement in Oscar Wilde's plays - Corrêa, Stephania Ribeiro do Amaral [UNESP] (2015)
This doctoral thesis proposes that all the plays written by Oscar Wilde (1854 - 1900), namely Vera or, The Nihilists (1880), The Duchess of Padua (1883), Lady Windermere's Fan (1892), Salomé (1892), A Woman of No Importance (1894), An Ideal Husband (1895) and The Importance of Being Earnest (1895), can be analysed according to the aesthetic theoretical perspective of which Wilde was one of the major exponents. The theoretical basis for the analysis is to be found in Wilde's critical essays, ‗The Truth of Masks' (1885), ‗The Decay of Lying' (1889), ‗Pen, Pencil and Poison' (1889) and ‗The Critic as Artist' (1890), which were later published in Intentions (1891). The present study has its foundations in my MA dissertation, Oscar Wilde: teoria e prática, concluded in April 2011. In that work, Wilde's play The Importance of Being Earnest was analysed from the same perspective, which made it possible to perceive the consistency between Oscar Wilde's theory and practice, as the results proved that both the structural and the linguistic elements of the play contain deep aesthetic features. The work developed here is thus intended to verify whether the transposition from theory to practice occurs in Wilde's dramatic work as a whole, or whether The Importance of Being Earnest is a specific and isolated case. Since it was possible to demonstrate that Wilde's plays are indeed consistent with his aesthetic principles, the study goes on to investigate the extent to which his dramatic composition may be associated with his own aesthetic precepts